Unusual Number of Phleboliths in a Lip Vascular Malformation - A Case Report - S M Balaji; Preetha Balaji (Wolters Kluwer Medknow Publications, 2022)
Rationale: Vascular malformation (VM) associated with jaws may cause jaw size discrepancy. Multiple phleboliths in VM are relatively rare. This case report aims to present one such case. Patient Concerns: A 33-year-old female patient sought surgical correction of her abnormally sized jaw and on examination, she was identified with VM. Diagnosis: Subsequent imaging tests revealed the presence of several phleboliths. Treatment: The patient was treated for an abnormal-sized mandible as well as partial removal of the superficial part of VM. Outcomes: The patient had satisfactory esthetics and there was less bleeding than anticipated. Take-away Lessons: VMs could cause jaw size discrepancy and the extent of the malformation could cause blood flow abnormalities leading to multiple phlebolith formation. Proper surgical planning and education of the patient are essential for successful treatment.